The Influence of Mobile Banking Service Quality on Customer Satisfaction - Pratama, Muhammad Rifky; Marliyah, Marliyah; Dharma, Budi (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to determine the effect of BSI Mobile Banking Service Quality on Customer Satisfaction (Case Study of Students of the Faculty of Islamic Economics and Business, UIN SUMATRA UTARA). The research method used is quantitative. The data source for this research is Bank Syariah Indonesia (BSI) mobile banking customers who are Fakultas Ekonomi Dan Bisnis Islam Students at Uin Sumatra Utara, and uses primary data. By using a collection technique through a questionnaire (questionnaire). The data analysis technique used in this study is to test the quality of the data, namely validity and reliability tests, multiple linear regression tests, and t tests. After going through quantitative procedures, this study obtained the reSumatra Utaralts that Mobile Banking Service Quality had an effect on Customer Satisfaction as evidenced by the correlation test which obtained reSumatra Utaralts of 0.000) <0.05. This means that the service quality variable has a positive and significant effect on customer satisfaction variables. Based on the reSumatra Utaralts of this study, the independent variable (Service Quality) of BSI Mobile has a significant effect on the dependent variable (Customer Satisfaction) of Faculty of Islamic Economics and Business Uin Sumatra Utara students.